CODE SWITCHING IN INDONESIA BILINGUAL EDUCATION - Rukmi, Nala Sita; Khasanah, Nurul (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2020)
Indonesian government policy supports the international of education at thesecondary level, consequently more institutions have commenced bilingual programs.Content is taught both in Bahasa Indonesia and English, making code-switching inclassroom discourse. The study was conducted at a single International school inSemarang, East Java, Indonesia. This case study explored in what ways and underwhat circumstances Indonesian teachers and learners use code-switching in theselected bilingual classroom and semi structured interviews with six-bilingual classstudents and teachers at an International secondary school in Semarang, East Java inIndonesia are used to get the data. The finding shows Teachers’ and students’ codeswitchingdemonstrated collectivist phatic functions ”“ for example, teachers codeswitchedto build rapport, remind students and reduce students’ anxiety, and studentscode-switched to show their solidarity and concern for their peers. Thus,interconnectedness was a key characteristic of code-switching by both teachers andstudents. This study argues that code-switching is not just about language deficiency,but involves intentional communicative purposes which support teaching andlearning. It can be concluded that code-switching can be a useful tool to bring aboutunderstanding of unfamiliar concepts and processes as well as the languageassociated with them.